2022
DOI: 10.1055/a-1911-8998
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrauma Emergencies during the SARS-CoV2 Pandemic at a Tertiary Medical Center: Analysis of Incidence and Outcome

Abstract: Objective: To assess the impact of the lockdown in Germany due to the COVID-19-pandemic on the incidence and the outcome of neurotrauma emergencies at a tertiary medical center. Material and Methods: From March 16th, 2020 (first lockdown in Germany) to January 31st, 2021, all neurosurgical emergencies were included and compared to a longitudinal case-cohort. Cases were descriptively recorded and retrospectively analyzed with respect to incidence and outcome. Results: All emergencies defined as polytrauma ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Probably, ongoing patient referrals in times of reduced ICU capacity and delayed treatment possibilities resulted in patients with an advanced stage of disease being admitted to university hospitals. This aspect was already shown in the first wave of the pandemic in Germany ( 21 , 29 , 30 ), and might explain the increased incidence of donor instability as a reason against utilized donations.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Probably, ongoing patient referrals in times of reduced ICU capacity and delayed treatment possibilities resulted in patients with an advanced stage of disease being admitted to university hospitals. This aspect was already shown in the first wave of the pandemic in Germany ( 21 , 29 , 30 ), and might explain the increased incidence of donor instability as a reason against utilized donations.…”
Section: Discussionmentioning
confidence: 69%
“…Potential DBD donors [defined as a patient with a devastating brain injury or lesion whose clinical condition is suspected to fulfill braindeath criteria ( 20 )] are recruited from the cohort of mechanically ventilated ICU-patients with a severe brain damage. The course of the disease does not allow postponement of admission, diagnosis, and therapy, especially since these patients usually cannot decide for themselves whether they will be admitted to a hospital ( 21 ). Reduced ICU capacities during the pandemic may therefore play a rather minor role in the admission of potential DBD donors (pDBD).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a longitudinal case-cohort study, performed at our tertiary medical referral center, showed an increase of 29% in number and severity of non-ischemic neurovascular emergencies (NINE), as well as on the incidence of neurosurgical traumata during the pandemic ( Lintas et al, 2200 ), ( Lintas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%